Motor Current Signature Analysis and Vibration Test on Rotating Machines of Chiller System at Uthm G2 Building - Khairul Anuar, Nadiah Farhah; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2021)
Rotating machines especially induction motors are widely used as industrial drives due to the self-starting factor, reliability, and economical. The three-phase induction motors are commonly used for complex systems such as generators or motors in chiller systems. However, these motors require maintenance as they enter a certain amount of time. Thus, motor testing can be done to provide the latest condition of the motors while it still running. The data obtained from the testing were be interpreted to detect any faults that occurred on the motors. This project provided testing of induction motors for the chiller system. Two parameters that be measured are the physical vibration of the motor and the phase current. Two sensors were used to take the vibration and current reading which are accelerometer and current clamp, respectively. The results were analyzed by using vibration analysis and motor current signature analysis (MCSA). Motor faults such as misalignment, unbalance and stator winding had been detected based on the magnitudes and respective frequencies presented in the spectra. Thus, machine testing should be taken seriously as it can assist maintenance work to ensure machines are long-lasting.